The Development of Moodle-Based Self Assessment to Measure Students’ Metacognition Ability (Unnes Science Education Journal, 2022)
This study aims to test the feasibility and analyze the characteristics of the instrument, as well as to measure the metacognition ability profile of each student and generally using a moodle-based self-assessment instrument. The research model used is ADDIE. The research data were obtained through expert validation, student responses, student answers to metacognition ability test questions, and the MCA-I questionnaire. Data were analyzed using the descriptive percentage technique. The results showed that the moodle-based self-assessment instrument was declared very feasible to measure students' metacognition abilities with a percentage of 92.14%. The self-assessment developed has general and specific characteristics. The general characteristics are; 1) valid; 2) reliable; 3) have a proportional level of difficulty; 4) has a good discrimination index, while the specific characteristics are: 1) based on moodle; 2) able to measure students' metacognition abilities by assessing themselves; 3) able to encourage students to use knowledge and metacognition strategies; 4) questions are contextual, clear, concise, and firm; 5) accompanied by pictures, graphs, and tables that make it easier for students; 6) the media is creative, interesting, and can motivate students; 7) objective; 8) economical and flexible; 9) practical; and 10) communicative. Based on the question test of metacognition ability, the profile of students' metacognition abilities, among others: 3 students are at level 1 with a percentage of 10.71%, 1 student is at level 2 with a percentage of 3.57%, and 8 students each at the ability level metacognition 3, 4, and 5 with a percentage of 28.57%. Based on the MCA-I Questionnaire, it was found that students generally had a well-developed metacognition profile with a percentage of 81.81%. The conclusion of this research is that self-assessment development products are found to be valid and reliable and able to measure students' metacognition ability profiles well.